Multilevel Hierarchical Structure Formed in the Film (Ti)/Substrate (SiC-Ceramics) System under Irradiation by an Intense Pulsed Electron Beam; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Ivanov Yu. F. Yuriy Fedorovich; Shugurov V. Vladimir; Kalashnikov M. P. Mark Petrovich; Leonov A. A. Andrey Andreevich; Teresov A. Anton; Petyukevich M. S. Mariya Stanislavovna; Polisadova V. V. Valentina Valentinovna (2018, 2018)
Title screen